Discrete Adaptive Nonswitching Reaching Law Algorithm for Sliding Mode Control of a Grid-Following Inverter - Sawiński, Albert; Leśniewski, Piotr; Chudzik, Piotr (Energies (Basel), 2025)
This paper extends one of the nonswitching-type reaching laws for discrete-time sliding mode control. The control task under consideration is the regulation of the grid current of the grid-following power inverter. A mathematical model of a plant is presented as an example of a microgrid. This system contains a T-type inverter, LCL filter, DC source, power grid connection and control system. The system tests were performed in a simulation environment. First, the methods known in the literature for implementing continuous sliding mode control are presented for the described problem, including stability analysis and implementation. Secondly, the well-known discrete sliding mode control algorithm based on the nonswitching reaching law type is discussed. The main part of this article consists of a proposed modification to the above algorithm. We consider the use of two separate regulation mechanisms: an adaptation of a specific control law parameter responsible for limiting the control signal and a mechanism for reducing the steady-state error. The aim of these procedures is to increase the quality of control, which, in turn, leads to an increase in the quality of energy transmitted in grids. The stability analysis is presented, as well as the simulation results. Finally, the results of all methods are compared and discussed, with conclusions drawn.